NIR-excited superoxide radical procreators to eradicate tumors by targeting the lyso-membrane. Issue 28 (26th June 2019) - Gurram, Bhaskar; Li, Miao; Li, Mingle; Gebremedhin, Kalayou H.; Sun, Wen; Fan, Jiangli; Wang, Jingyun; Peng, Xiaojun
Abstract : NIR alkylated cationic photosensitizers targeting at lyso-membrane for eradicating tumor cells through prominent superoxide radical generation (type-I PDT) via lysosome disruption pathway. Abstract : NIR photosensitizers have been used as potential photo-activators to inhibit cancer cells as well as the growth of various types of bacteria. Herein, we first designed NIR alkylated cationic photosensitizers (Et-NB-C12 >Et-NB-C18 andMt-NB-C12 >Mt-NB-C18 ), which target the lyso-membrane for the eradication of tumor cells through prominent superoxide radical generation (type-I PDT) via the lysosome disruption pathway. The O2 − ˙ radical sensors (DHE and DHR123) exhibited a 10-fold increment in fluorescence intensity in solution and MCF-7 cells after treatment with NIR cationic photosensitizers under 660 nm irradiation.Et-NB-C12 >Et-NB-C18 preferentially targeted the lyso-membrane, resulting in O2 − ˙ radical generation in the lyso-membranes during PDT irradiation. Furthermore, lysosomal disruption, flow cytometry, and MTT assays demonstrated that the influential generation of O2 − ˙ radicals in cancer cells initiated cell apoptosis and further cell death after irradiation with PDT light at 660 nm. The inhibition activity ofEt-NB-C12 >Et-NB-C18 in MCF-7 cells showed stronger anticancer efficiency (IC50 0.08 > 0.12 μM) than that ofMt-NB-C12 >Mt-NB-C18 (IC50 = 0.30 > 0.32 μM), lower than that of Ce6 (1.28 μM). In particular, Et-NB-C12 can be effectively utilized in in vivo imaging, and it exhibits outstanding anticancer properties during both ex vivo and in vivo photodynamic therapy.